2015
DOI: 10.1038/jcbfm.2015.16
|View full text |Cite
|
Sign up to set email alerts
|

Tat-NR2B9c Prevents Excitotoxic Neuronal Superoxide Production

Abstract: The Tat-NR2B9c peptide has shown clinical efficacy as a neuroprotective agent in acute stroke. Tat-NR2B9c is designed to prevent nitric oxide (NO) production by preventing postsynaptic density protein 95 binding to N-methyl-D-aspartate (NMDA) receptors and neuronal nitric oxide synthase; however, PSD-95 is a scaffolding protein that also couples NMDA receptors to other downstream effects. Here, using neuronal cultures, we show that Tat-NR2B9c also prevents NMDA-induced activation of neuronal NADPH oxidase, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 18 publications
0
28
0
Order By: Relevance
“…Interestingly, the TAT-fused arginine-rich NADPH oxidase complex inhibitor peptide gp91ds-TAT (CSTRIRRQL-TAT-NH2; net charge with NH2 group +12) inhibited neuronal NMDA induced superoxide production to a greater extent than TAT-NR2B9c, while the TAT-fused non arginine-rich scrambled peptide (CSFNSYELGSLCY-TAT) did not. The Chen et al (2015) study also showed that TAT-NR2B9c did not inhibit NMDA induced neuronal calcium influx.…”
Section: Examination Of Studies Using Cpp-fused To Neuroprotective Pementioning
confidence: 88%
See 2 more Smart Citations
“…Interestingly, the TAT-fused arginine-rich NADPH oxidase complex inhibitor peptide gp91ds-TAT (CSTRIRRQL-TAT-NH2; net charge with NH2 group +12) inhibited neuronal NMDA induced superoxide production to a greater extent than TAT-NR2B9c, while the TAT-fused non arginine-rich scrambled peptide (CSFNSYELGSLCY-TAT) did not. The Chen et al (2015) study also showed that TAT-NR2B9c did not inhibit NMDA induced neuronal calcium influx.…”
Section: Examination Of Studies Using Cpp-fused To Neuroprotective Pementioning
confidence: 88%
“…In a recent study (Chen et al, 2015), TAT-NR2B9c was shown to inhibit neuronal NMDA induced superoxide production by blocking the activation of the membrane-bound NADPH oxidase (nicotinamide adenine dinucleotide phosphate-oxidase) complex. It was proposed that the TAT-NR2B9c peptide by inhibiting the PSD-95/ NR2B9c interaction blocked PSD-95 adaptor protein APPL1 (adaptor protein, phosphotyrosine interaction, PH domain and leucine zipper containing 1) coupling with PI3K (phosphatidylinositol-4,5-bisphosphate 3-kinase), thereby inhibiting PKCζ (protein kinase C) to phosphorylate the NADPH oxidase subunit protein p46 phox , which is required for activation of the complex.…”
Section: Examination Of Studies Using Cpp-fused To Neuroprotective Pementioning
confidence: 99%
See 1 more Smart Citation
“…Our results showed that tatCN21 mediated neuroprotection was accompanied by decreased membrane PSD95 aggregation, implying that decreased PSD95 membrane localization after GCI could contribute to the neuroprotective properties of tatCN21. Indeed, previous study showed that disruption of membrane aggregation of PSD95 and PSD95-NR2B binding following ischemic stroke conferred neuroprotection (Chen et al , 2015). Further studies should investigate whether tatCN21 affects the association of NR2B and PSD95 at the synaptic membrane, as well as other PSD95 associated contributors to ischemic injury.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 An important downstream consequence is that Tat-NR2B9c attenuates ROS induced by NMDAR activity. 12,13 The preclinical efficacy of Tat-NR2B9c as a stroke neuroprotectant has been validated by us and others in several stroke models in rats. 2,4,10,[14][15][16] and in comprehensive studies in non-human primates that provided strong evidence of efficacy.…”
Section: Introductionmentioning
confidence: 99%